ASOSIASI LAMUN DAN ECHINODERMATA PADA EKOSISTEM PADANG LAMUN CAGAR ALAM LEUWEUNG SANCANG, JAWA BARAT - Tri Dewi K. Pribadi; Raden Wandha Humaira; Nenci Haryadi; Archie S. Eka Buana; Yudi Nurul Ihsan (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTThe Leuweung Sancang Nature Reserve has ecosystem diversity, including seagrass beds, with a variaety of natural resources that are important to be preserved. Apart from being a food source for herbivorous organisms, seagrass beds also function as shelter and breed for many marine invertebrates, including Echinoderms. Association between Echinoderms and seagrass was observed in this study to investigate the interaction. Sampling was carried out in 1x1 m2 plots which were placed in 3 transect lines of 250 m long, with a plot intervals of 25 m on each transect line. The transect line extended from the beach heading to the shore, and was carried out in 4 different stations, namely Ciporeang, Cipunaga, Cikolomberan, and Cipangikisan. Observation had been done to determine diversity, density, coverage, and evenness of both seagrass and Echinoderms, thus to study the correlation between them. The results showed that there were 2 seagrass species, Thalassia hempricii and Cymodocea rotundata, and there were 2 families of Echinoderms: Ophiocomidae and Holothuridae. Result of Rank–Spearman correlation coefficient showed possitive association between seagrass and echinoderms in all stations being observed, but only in Cikolomberan that showed significantly high association.Keywords: association, Echinoderms, Leuweung Sancang, seagrass.ABSTRAKCagar alam Leuweung Sancang memiliki keanekaragaman ekosistem, termasuk padang lamun, dengan berbagai sumber daya alam di dalamnya yang penting untuk dijaga kelestariannya. Selain sebagai sumber makanan bagi organisme herbivor, padang lamun juga berfungsi sebagai tempat berlindung dan berkembang biak bagi banyak invertebrata laut, termasuk Echinodermata. Keterkaitan antara Echinodermata dan lamun diobservasi pada studi ini untuk dipelajari untuk melihat interaksinya. Pengambilan sampel dilakukan dalam plot 1 x 1 m2 yang ditempatkan pada 3 garis transek masing-masing sepanjang 250 m dengan interval plot sejauh 25 m pada setiap garis transek. Garis transek terbentang dari pantai menuju laut, dan dilakukan pada 4 stasiun yang berbeda, yaitu Ciporeang, Cipunaga, Cikolomberan, Cipangikisan. Pengamatan dilakukan untuk menentukan keragaman, kepadatan, frekuensi, tutupan dan kemerataan lamun dan Echinodermata, untuk kemudian dilihat asosiasinya. Hasil menunjukkan bahwa di keempat stasiun pengamatan ditemukan 2 spesies lamun yaitu Thalassia hempricii dan Cymodocea rotundata dan 2 famili Echinodermata: Ophiocomidae dan Holothuridae. Hasil koefisien korelasi Rank-Spearman pada keempat stasiun pengamatan menunjukan adanya asosiasi positif antara lamun dan Echinodermata, namun hanya di Cikolomberan yang memiliki asosiasi tinggi dan signifikan.Kata kunci: asosiasi, Echinodermata, Leuweung Sancang, lamun.